HIV-1 Populations in Semen Arise through Multiple Mechanisms. - Jeffrey A Anderson (Public Library of Science (PLoS), 2010)
HIV-1 is present in anatomical compartments and bodily fluids. Most transmissions occur through sexual acts, making virus in semen the proximal source in male donors. We find three distinct relationships in comparing viral RNA populations between blood and semen in men with chronic HIV-1 infection, and we propose that the viral populations in semen arise by multiple mechanisms including: direct import of virus, oligoclonal amplification within the seminal tract, or compartmentalization. In addition, we find significant enrichment of six out of nineteen cytokines and chemokines in semen of both HIV-infected and uninfected men, and another seven further enriched in infected individuals. The enrichment of cytokines involved in innate immunity in the seminal tract, complemented with chemokines in infected men, creates an environment conducive to T cell activation and viral replication. These studies define different relationships between virus in blood and semen that can significantly alter the composition of the viral population at the source that is most proximal to the transmitted virus.